Correction to: Time to move? Factors associated with burden of care among informal caregivers of cognitively impaired older people facing housing decisions: secondary analysis of a cluster randomized trial - Boucher, Alexandrine; Haesebaert, Julie; Freitas, Adriana; Adekpedjou, Rhéda; Landry, Marjolaine; Bourassa, Henriette; Stacey, Dawn; Croteau, Jordie; Painchaud Guérard, Geneviève; Légaré, France (Université d'Ottawa | University of Ottawa, 2020)
Following publication of the original article [1], we have been notified that one of the authors’ given name and last names are reversed and misspelled and thus not reflected correctly (given name now is Painchaud-Guérard and it should be Geneviève and last name now is Geneviève and it should be Painchaud Guérard).